Aspiring Ballerinas and Implications for Counselling Practice - Sandham, Tricia J.; Nicol, Jennifer J. (Canadian Journal of Counselling and Psychotherapy, 2014)
Preparing for a professional ballet career requires dedication, discipline, and single-minded focus. But as training becomes increasingly competitive, many dancers must give up their aspiration to become a professional. The aim of this study is to share the stories of elite female dancers who, despite years of intense training, were unable to achieve a professional dancing career. Five women volunteered to tell their stories by participating in multiple semistructured interviews, during which they also shared personal mementos such as dance photographs, pointe shoes, and dance competition medals. Their stories were analyzed thematically and represented with illustrative quotes. Findings suggested that giving up the dream to dance professionally after years of training resulted in many losses; most striking was the loss of identity. Implications for counsellors working with amateur female dancers who were unable to achieve a performing career are discussed.